Products in the category of sets
For any sets \(X\) and \(Y\), let \(Y^X\) denote the set of all functions with domain \(X\) and image contained in \(Y\).1
Let sets \(A\) and \(B\) be given.
For sets \(Q\) and functions \(q_A\) and \(q_B\), we define the predicate
If \(\mathtt{Compatible}_{A,B}(P,p_A,p_B)\) is true, define the predicate
Theorem
If \(\mathtt{Prod}_{A,B}(P,p_A,p_B)\) is true and \(\mathtt{Prod}_{A,B}(Q,q_A,q_B)\) is true, then there is a bijection \(P \to Q\).
Proof
Because \(\mathtt{Prod}_{A,B}(P,p_A,p_B)\) is true and \(\mathtt{Compatible}_{A,B}(Q,q_A,q_B)\) is true, there is a unique function \(f \in P^Q\) such that $$ \begin{equation} p_A \circ f = q_A \label{qA} \end{equation} $$ and $$ \begin{equation} \quad p_B \circ f = q_B. \label{qB} \end{equation} $$
Because \(\mathtt{Prod}_{A,B}(Q,q_A,q_B)\) is true and \(\mathtt{Compatible}_{A,B}(P,p_A,p_B)\) is true, there is a unique function \(g \in Q^P\) such that $$ \begin{equation} q_A \circ g = p_A \label{pA} \end{equation} $$ and $$ \begin{equation} \quad q_B \circ g = p_B. \label{pB} \end{equation} $$
From \(f \in P^Q\) and \(g \in Q^P\), it follows that \(f \circ g \in P^P\). Define $$\phi = f \circ g, \qquad \phi \in P^P.$$
From \(\phi \in P^P\) and \(p_A \in A^P\), it follows that \(p_A \circ \phi \in A^P\). From \(\phi \in P^P\) and \(p_B \in B^P\), it follows that \(p_B \circ \phi \in B^P\). Therefore, \(\mathtt{Compatible}_{A,B}(P,p_A \circ \phi,p_B \circ \phi)\) is true.
Because \(\mathtt{Prod}_{A,B}(P,p_A,p_B)\) is true and \(\mathtt{Compatible}_{A,B}(P,p_A \circ \phi,p_B \circ \phi)\) is true, there is a unique function \(h \in P^P\) such that $$ \begin{equation} p_A \circ h = p_A \circ \phi \label{pAphi} \end{equation} $$ and $$ \begin{equation} p_B \circ h = p_B \circ \phi. \label{pBphi} \end{equation} $$
But $$ \begin{align*} p_A \circ \phi&= p_A \circ (f \circ g)\\ &=(p_A \circ f) \circ g \quad \textrm{by associativity}\\ &=q_A \circ g \quad \textrm{by \eqref{qA}}\\ &=p_A \quad \textrm{by \eqref{pA}} \end{align*} $$ and $$ \begin{align*} p_B \circ \phi&=p_B \circ (f \circ g)\\ &=(p_B \circ f) \circ g \quad \textrm{by associativity}\\ &=q_B \circ g \quad \textrm{by \eqref{qB}}\\ &=p_B \quad \textrm{by \eqref{pB}}. \end{align*} $$
Thus \(\eqref{pAphi}\) is equivalent with $$ p_A \circ h = p_A $$ and \(\eqref{pBphi}\) is equivalent with $$ p_B \circ h = p_B. $$
Thus, \(\textrm{id}_P \in P^P\) satisfies \(\eqref{pAphi}\) and \(\eqref{pBphi}\). Because \(h\) is the unique element of \(P^P\) satsifying \(\eqref{pAphi}\) and \(\eqref{pBphi}\), it follows that $$h=\textrm{id}_P.$$
From \(g \in Q^P\) and \(f \in P^Q\), it follows that \(g \circ f \in Q^Q\). Define $$\psi = g \circ f, \qquad \psi \in Q^Q.$$
From \(\psi \in Q^Q\) and \(q_A \in A^Q\), it follows that \(q_A \circ \psi \in A^Q\). From \(\psi \in Q^Q\) and \(q_B \in B^Q\), it follows that \(q_B \circ \psi \in B^Q\). Therefore, \(\mathtt{Compatible}_{A,B}(Q,q_A \circ \psi,q_B \circ \psi)\) is true.
Because \(\mathtt{Prod}_{A,B}(Q,q_A,q_B)\) is true and \(\mathtt{Compatible}_{A,B}(Q,q_A \circ \psi,q_B \circ \psi)\) is true, there is a unique function \(k \in Q^Q\) such that $$ \begin{equation} q_A \circ k = q_A \circ \psi \label{qApsi} \end{equation} $$ and $$ \begin{equation} q_B \circ k = q_B \circ \psi. \label{qBpsi} \end{equation} $$
But $$ \begin{align*} q_A \circ \psi&=q_A \circ (g \circ f)\\ &=(q_A \circ g) \circ f \quad \textrm{by associativity}\\ &=p_A \circ f \quad \textrm{by \eqref{pA}}\\ &=q_A \quad \textrm{by \eqref{qA}} \end{align*} $$ and $$ \begin{align*} q_B \circ \psi&=q_B \circ (g \circ f)\\ &=(q_B \circ g) \circ f \quad \textrm{by associativity}\\ &=p_B \circ f \quad \textrm{by \eqref{pB}}\\ &=q_B \quad \textrm{by \eqref{qB}}. \end{align*} $$
Thus \(\eqref{qApsi}\) is equivalent with $$ q_A \circ k = q_A $$ and \(\eqref{qBpsi}\) is equivalent with $$ q_B \circ k = q_B. $$
Thus, \(\textrm{id}_Q \in Q^Q\) satisfies \(\eqref{qApsi}\) and \(\eqref{qBpsi}\). Because \(k\) is the unique element of \(Q^Q\) satsifying \(\eqref{qApsi}\) and \(\eqref{qBpsi}\), it follows that $$k=\textrm{id}_Q.$$
-
Indeed, this makes sense when one or both of \(X\) or \(Y\) is the empty set. ↩
-
Category Theory: a concise course. 5. Product, Coproduct, Exponential | Charlotte Aten, Venanzio Capretta, and William DeMeo ↩